Optimal Zoning in Spatial Differentiation - Hamoudi, Hamid; Rodríguez, Isabel; Sanz Martín-Bustamante, Marcos (Estudios de Economía, 2017)
This study analyzes optimal zoning policy in a duopolistic spatial competition framework for both circular and linear spaces. A regulator is introduced in the third stage of the price-location game through a welfare function to model zoning preferences from firms and consumers. An equilibrium outcome is then found for both spatial configurations. When the regulator is inclined to favor consumers (consumer-oriented) both firms are restricted to locate at one point to serve the whole market. Nevertheless, when the preferences of the regulator are biased towards firms (firm-oriented) the zoning area is maximized, with both firms being located at the market boundaries. The equilibrium outcome confirms location patterns found in real life situations under a non-neutral regulator.